REDESIGN SHEEP CAGE LAYOUT USING THE ACTIVITY RELATIONSHIP CHART METHOD & SHEEP HUSBANDRY SYSTEM USING MACRO ERGONOMIC APPROACH - Ricky Yoseptry; Sukendar Sukendar; Jejen Ahmad Jaelani (SEAN Institute, 2023)
Most of the population in Indonesia, both in urban areas, but especially in rural areas, many people invest in the livestock sector by taking advantage of the fertility of the soil they have for farming and some use it for raising livestock because the available feed is quite abundant in the types of grasses and leaves that are available. usually used for animal feed. One of them is raising sheep, this is because the sale value of sheep is quite high, and the consumption of lamb meat, especially for the regency, is quite high. As done by Young Farmer Farm, this farm which is located in the village of Cibiru Kindul, Bandung City, focuses on raising sheep, fattening sheep for beef, and making organic fertilizer from sheep manure on the farm. Most of the conditions of Indonesian livestock are only based on experience, meaning that they do not pay attention to the provisions in animal husbandry. This is the cause of the lack of good quality livestock systems in Indonesia. Therefore it is very important to improve the livestock system in order to obtain better quality and quantity of productivity. Activity analysis used to analyze input and output process flow of the livestock system uses the Activity relationship chart method which is a qualitative approach developed by Mucher. Is a way to analyze the flow of work, namely the relationship relationship with benchmarks degree of closeness of the relationship between one activity to another, in this study the data were obtained through observation and approved by the management of the farm. Macro ergonomics is a concept by defining a top-down sociotechnical system to produce a work system. The use of macro ergonomics is used to analyze the problems found in young farmer farm sheep so that in the end a number of suggestions for improvements related to the problems are obtained. The results of this research show that the problems that are considered to have a major impact on the sustainability of livestock are the conditions of the sheep pens, the process of feeding and drinking the sheep, caring for the sheep and the process of disposal and waste management. Improving the condition of the cage is done by relaying the condition of the cage, namely repositioning according to the provisions. Improving the process of feeding and drinking is carried out based on the provisions of feeding according to the rules. Treatment improvements were carried out by providing a quarantine process and sheep bathing. Improving the process of disposal and waste management is carried out by maximizing the use of manure as organic fertilizer.